From Ratios to Constructs: Sector-Contingent Financial Health Indices via Factor Analysis (KASBIT Business Journal, 2026)
This paper investigates the reclassification of financial ratios through Exploratory Factor Analysis (EFA), trying to uncover empirical groupings that best describe the financial dynamics within the specific industry. We collected data of 19 commonly used financial ratios from 39 firms from two industries, including 22 from the FMCG and 17 from the Cement Sector, using 22 years from 2003 to 2024 through the audited annual accounts. The empirical findings reveal seven distinct categories within the FMCG sector and 6 within the Cement Sector, differing substantially from the traditional academic classification of 4 standard categories. These findings suggest that the behavior of financial ratios is sector-specific and classification in finance textbooks lacks empirical robustness if applied across different industry contexts. The empirical results also underscore the need for an industry-specific framework for financial analysis and raise critical implications for analysts, investors and educators to bridge the gap between the theoretical constructs and empirical financial analysis.